SUSTAINABLE VALUE CREATION IN LATVIA, LITHUANIA AND ESTONIA: COMPARATIVE ANALYSIS OF ECONOMIC RETURN FROM THE USE OF ECONOMIC, SOCIAL AND ENVIRONMENTAL RESOURCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Baltic neighbouring countries Latvia, Lithuania and Estonia all over the world are considered as brotherly nations that have similar historical events and political economic system. However, for the period of 25 years after gaining their independence from the Soviet Union in 1990, these countries have been implementing different socio-economic development models. It can be concluded on the achieved development results by the world recognized and widely used index indicators as Human Development Index (HDI), Global Competitiveness Index (GCI), Doing Business Index (DBI), revealing a trend that Estonia according to the socio-economic indicators is a step ahead of both Latvia and Lithuania. However, the above-mentioned indices calculation does not include the environmental indicators (HDI report includes Environmental Sustainability subindex, which is calculated separately) that cannot take account of national sustainable development which is becoming increasingly important under the conditions of global resource scarcity. The aim of the research is to determine sustainability of Latvia, Lithuania and Estonia, using the Sustainable Value (SV) approach, calculating how efficiently and with what return (Country's Gross Domestic Product) their economic, social and environmental resources are consumed. SV is a value-based assessment that measures contributions to sustainability in monetary terms while being able to use non-monetary environmental and social input variables. Calculating SV of Latvia, Lithuania and Estonia, the author has used 10 indicators of 2014 that cover the economic, social and environmental dimensions of sustainability, using the average efficiency of these countries as benchmark. As a result the author concluded that, overall, Latvia and Lithuania have almost equal footing with the Return to Cost Ratio (RCR) results, respectively 1.41 and 1.32 (>1 means that resources are used more efficiently than the benchmark), while Estonia's RCR value is 0.52 (